Seeking Help for Harm from Others' Drinking in Five Asian Countries: Variation Between Societies, by Type of Harm and by Source of Help - Waleewong, O.; Laslett, Anne-Marie; Chenhall, R.; Room, R. (Oxford University Press, 2018)
Aims: This study aims to measure the prevalence rates and patterns of help-seeking behavior as a consequence of being harmed by drinkers in five Asian countries (India, Sri Lanka, Vietnam, Lao PDR and Thailand).Methods: A total of 9832 respondents aged 18-65 years from the WHO/ThaiHealth Collaborative Project were surveyed between 2012 and 2014 about their experiences of being negatively affected due to another's drinking, and whether and where they sought help, focusing on four adverse aspects of harms from others' drinking.Results: The prevalence of seeking help from any source in the past year due to harm from others' drinking ranged from 7% to 20%. The most common service used by those who were affected by other people's drinking was asking for help from friends, followed by calling the police and using health-related services. The largest proportion of help-seeking was among those reporting property harm, followed by those being harmed physically and sexually by drinkers.Conclusion: Given a wide range of harms from others' drinking in the general population and different needs of those affected, prevalence rates for help-seeking behavior due to others' drinking in South and South East Asian countries were low and the help sought was often informal. There is a large knowledge gap in our understanding of the mechanisms of help-seeking behavior and the pathways for access to help among those affected. Further studies are important for enhancing the social response services available and making these more accessible to those who need help.